Physiological Response of the Target Stemborer Chilo suppressalis to Elevated CO2 as Reared with Transgenic Bt Rice during Different Plant Growth Stages - Yanmin Liu; Yanhui Wang; Sihan Li; Boxuan Xie; Geng Chen; Fajun Chen (Agronomy, 2023)
Transgenic Bt rice (abbr. Bt rice) has provided a powerful tactics to control the striped stemborer Chilo suppressalis as one key lepidopteran pest in the paddyfields of China. Globally rising carbon dioxide (i.e., CO2) concentration has been predicted to affect the Cry protein contents in plant tissues of Bt rice and thus might affect its control efficiency to target insect pests. To reveal the resistance ability and the corresponding mechanism of C. suppressalis to Bt rice during different growth stage under elevated CO2 (eCO2), we carried out this experiment to measure the Bt toxin contents in Bt rice stems grown under ambient CO2 (aCO2) (400 ppm) and eCO2 (800 ppm) at seedling, tillering and heading stages, and to observe the larval mortality and bioassay the activity of midgut protease and the expression levels of Bt-toxin-receptor genes, aminopeptidases (APNs) in C. suppressalis larvae. Compared with aCO2, eCO2 increased the Bt-toxin content of Bt rice at seedling stage (+6.66%), and decreased that at heading stages (−13.99%), and significantly reduced the Bt-toxin content at tillering stage (−15.21%). And the larval mortality of C. suppressalis was lower as reared with Bt rice stems during tillering stage grown under eCO2 in contrast to aCO2. In addition, eCO2 significantly increased the activity of total protease, tryptase-like enzyme and aminopeptidase of C. suppressalis larvae fed on Bt rice during seedling stage, and significantly reduced the activity of tryptase-like enzyme and aminopeptidase of C. suppressails larvae fed on Bt rice during tillering and heading stages respectively. Moreover, eCO2 significantly increased the expression level of APN1 and APN5 of C. suppressails larvae fed on Bt rice during seedling stage, and significantly reduced the expression level of APN5 of C. suppressalis larvae fed on Bt rice during tillering and heading stages respectively. In summary, the control efficiency of Bt rice to target insect pests under eCO2 showed a downward trend during tillering and heading stages, and especially during tillering stage.